Financial Technology Strategy for Islamic Banking Competitiveness - Muhammad Luqman Hakim (Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Purpose - Analyze the development of Financial Technology and Islamic banking financial data to have implemented financial technology for customers and the profits achieved.Method - This research is qualitative with a literature study connected with the phenomena in Islamic banking to implementing financial technology.Result - Show that the level of service and financial technology is valid, practical and efficient for customers and benefits for Islamic banking. Implication - Technological developments can have benefits for users according to their needs. One of the benefits is related to efficiency in use. Financial institutions use technology to make easier for their customers in digital-based financial transactions. Originality- This research studies the development of Islamic bank performance, the development of Islamic bank financing from the number of ATMs, one form of Islamic banking financial technology in Indonesia.